2015
DOI: 10.1117/1.nph.2.4.041402
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte structure and distribution in the cerebral cortex revealed by high-resolution imaging of transgenic mice

Abstract: Pericytes are essential for normal brain function, but many aspects of their physiology remain enigmatic due to a lack of tools to genetically target this cell population. Here, we characterize brain pericytes using two existing Cre-recombinase driver mouse lines that can serve distinct purposes in cerebrovascular research. One line expresses an inducible version of Cre under the NG2 proteoglycan promoter, which provides the sparse labeling necessary to define the morphology of single cells. These mice reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
285
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(322 citation statements)
references
References 41 publications
(36 reference statements)
26
285
0
Order By: Relevance
“…As in past studies, we observed a heterogeneity of mural cell types, ranging from ring-shaped smooth muscle cells on arterioles to pericytes with varying degrees of vessel coverage on pre-capillary arterioles and capillaries (Grant et al, 2017; Hartmann et al, 2015). In this study, we focused on pericytes adorning the mid-capillary regions (Figure 1C).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As in past studies, we observed a heterogeneity of mural cell types, ranging from ring-shaped smooth muscle cells on arterioles to pericytes with varying degrees of vessel coverage on pre-capillary arterioles and capillaries (Grant et al, 2017; Hartmann et al, 2015). In this study, we focused on pericytes adorning the mid-capillary regions (Figure 1C).…”
Section: Resultssupporting
confidence: 81%
“…Recent high-resolution optical imaging studies have shown that brain capillary pericytes are organized as a cellular chain along the capillary bed (Hartmann et al, 2015; Hill et al, 2015). Each pericyte extends thin, elongated processes from distinct ovoid cell bodies to contact and communicate with multiple underlying endothelial cells (Allt and Lawrenson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Confocal images were obtained with a Zeiss LSM 880 imaging system under a 63× water-immersion objective. Cerebral capillaries, precapillary arterioles, and postcapillary venules were identified according to features established in earlier publications (5,43,44) and briefly as follows: (i) αSMA-negative vessels with a vascular lumen diameter < 10 μm were identified as capillaries; (ii) αSMA-positive vessels terminating before αSMA-negative capillaries were identified as precapillary arterioles; and (iii) αSMA-negative vessels with a vascular lumen diameter 10-20 μm were identified as postcapillary venules.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of the cortical angioarchitecture in mice expressing fluorescent proteins under control of the NG2 and PDGFRβ promoters have identified several pericyte subpopulations including VSMC-pericyte hybrid on pre-capillary arterioles, thin strand helical mid-capillary pericyte, and mesh pericyte with a stellate morphology on post-capillary arterioles and venules 19,20 . Future single-cell RNA-seq and proteomic studies as used successfully to characterize subpopulations of cortical progenitor cells 23 and drug resistant tumor cells 24 , may also contribute to better understanding of different pericyte subtypes.…”
Section: Pericytes: Characterization Function and Dysfunctionmentioning
confidence: 99%